PKM TINGKAT PENGETAHUAN SERTA PENGAPLIKASIAN WARMING UP DAN COOLING DOWN DENGAN ANGKA KEJADIAN CEDERA PADA ATLET KARATE PPLP JAWA TENGAH - Triyanita, Maya; Pambudi, Restu Arya; Ali, Mohammad (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2024)
Every sport has stages that need to be done to avoid injury, such as warming up, core movements and cooling down. The heating and cooling carried out must have the right duration and be effective. Knowledge has a role in reducing the risk of injury. With good knowledge, athletes can carry out injury prevention methods according to the experience and knowledge gained through various media. To find out the level of heating and cooling knowledge, it can be measured using a questionnaire. This service aims to share knowledge with athletes about what warming up and cooling down is so that it can reduce the number of injuries among Central Java PPLP karate athletes.